Blunt thoracic trauma and cardiac injury in the athlete: Contemporary management - De Gregorio, C.; Magaudda, L. (The Journal of Sports Medicine and Physical Fitness, 2018)
Commotio cordis and cardiac injuries are rare events usually following a chest blunt traumas during sports activities. Various etiologies have been identified to cause electrical (commotio cordis) and/or structural (contusion and further injuries) damage, but high-velocity tools such as baseballs or hockey pucks (also called projectiles) have been chiefly identified. Clinical consequences are challenging, varying from uncomplicated supraventricular arrhythmias to cardiac wall rupture. Ventricular fibrillation is the most remarkable outcome leading to cardiac arrest in some individuals. In this article, up-to-date epidemiological and pathophysiological issues are discussed, along with the most suitable assistance protocols of the injured athlete in the sports arena. Current knowledge about traumatic sports injuries and ensuing cardiovascular sequelae made significant steps forwards than in the past. The majority of athletes (especially the youngest ones) wearing chest protectors are usually preserved from serious outcomes and sudden cardiac death, but further technical effort is encouraged to attain more satisfactory barriers against projectile`s impact. Educational campaigns among students, closer team surveillance, implementation of the sports arenas with adequate rescue devices and medical assistance remain mandatory items in contact sports activity.